Development Of Physics Learning Media PHY-ART (Physics With Augmented Reality Technology) To Empower Student’s Laboratory Skills - Batulieu Muhammad Yoggi Prastya; Sri Budiawanti; Daru Wahyuningsih (STKIP Singkawang, 2023)
The world of education requires newest learning media when technology is growing. The development of Physics learning media with Augmented Reality technology is a solution to bring forward education. The development of Physics learning media PHY-ART aims to describe the development of Augmented Reality technology for physics learning media, and find out the impact of implementing Physics learning media PHY-ART on improving students' laboratory skills. A total of 78 high school students were researched with pre-test and post-test to determine the students' laboratory skills before and after. After using Physics learning media PHY-ART, it is known that AR technology improves students' laboratory skills. The physics learning media PHY-ART can be used by educational practitioners to improve laboratory skills and can be used as an alternative in the variety of learning media.